Curiosity as an intellectual and ethical virtue - Yiğit, Safiye. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
In this study, I claim that curiosity is an ethical and intellectual virtue that is necessary for any well-lived life. I distinguish curiosity from other types of desiring to know that could emerge from pragmatic reasons, necessity, or an idle urge to know, and any other reason except the ones that comes from within the individual and that will not leave one until it is satisfied. Restricted as it might sound, I define curiosity as an "intrinsic desire to know in order to understand" and claim that a flourishing life is not possible without it. Such a curiosity has two distinguishing marks: in any case of curiosity there must be (a) an intrinsic interest to know and (b) a genuine aim of understanding. Since curiosity is taken to be the gateway to the ultimate epistemic end, understanding, I briefly explore the distinctions between knowledge and understanding and propose understanding as the human telos/ergon. Another claim I make is that curiosity is intrinsically valuable regardless of the final attainment of knowledge and it is also pointed out that non-pragmatic knowledge would lose any significance and value if we were not curious beings. Probably the most original claim of the thesis will appear in the part where I argue that knowledge and curiosity form "an organic unity" and neither is correctly assessable without the other. I will then draw attention to the fact that curiosity is perhaps the ground of the possibility of theoretical knowledge and it should be valued as much as or even more than we value knowledge. Then, I explore intellectual virtues in the sense the term has recently gained in Virtue Epistemology and after l succinctly survey the newly flourishing field, the claim that curiosity is an intellectual virtue will take place. This claim will be made based on the fact that curiosity is necessary to be able to question and make sense of any corresponding knowledge. Even if one had every other intellectual virtue such as open-mindedness, perseverance, and the like, if one lacks curiosity, the epistemic endeavor would end even before it starts. In addition to being an intellectual virtue, the other central claim I have is that curiosity is an ethical virtue. Controversial as this claim may be, I attempt to show that there is ample reason for considering curiosity as a virtue that makes our lives "eudaimon". As side issues, I also deal with the conditions under which curiosity is totally satisfiable and whether or not such satisfaction is desirable. Here, the "utopia paradox" that awaits human beings provided that all curiosity is eliminated from our world is sketched out and this will give support to my thesis that curiosity is necessary for a good life. Lastly, I address the problem of deviant curiosity and give an account of why curiosity could still be considered as an ethical virtue despite the possible negative consequences.
Keywords: Curiosity.; Learning.